Porphyromonas gingivalis Induces Apoptosis and Autophagy via ER Stress in Human Umbilical Vein Endothelial Cells - Hirasawa, Masaaki; Kurita-Ochiai, Tomoko (Mediators of Inflammation, 2018)
It has been reported that periodontitis is associated with an increased risk of atherosclerosis. Accumulating evidence suggests that endothelial dysfunction is an early marker for atherosclerosis. To determine how periodontal infections contribute to endothelial dysfunction, we examined the effect of Porphyromonas gingivalis on human umbilical vein endothelial cells (HUVEC). P. gingivalis significantly suppressed the viability of HUVEC, induced DNA fragmentation and annexin V staining, and increased caspase-3, caspase-8, and caspase-9 activities. P. gingivalis also increased the expression of GADD153 and GRP78 and caspase-12 activity. Further, P. gingivalis induced autophagy, as evidenced by increased LC3-II and Beclin-1 levels. The suppression of P. gingivalis-induced autophagy by silencing of LC3 with siRNA significantly increased P. gingivalis-induced apoptosis. ER stress inhibitor, salubrinal, suppressed apoptosis and autophagy by inhibiting P. gingivalis-induced DNA fragmentation and LC3-II expression. These data suggest that P. gingivalis infection induces ER stress-mediated apoptosis followed by autophagic response that protects HUVEC from P. gingivalis-mediated apoptosis, potentially amplifying proatherogenic mechanisms in the perturbed vasculature.